2022
DOI: 10.3390/nu14173621
|View full text |Cite
|
Sign up to set email alerts
|

Overweight/Obesity Prevalence among Under-Five Children and Risk Factors in India: A Cross-Sectional Study Using the National Family Health Survey (2015–2016)

Abstract: The occurrence of overweight and obesity has increased in recent years in India. In this study, we investigate the prevalence and associated risk factors of overweight/obesity among children aged 0–59 months in India. Using data from the 2015–2016 National Family Health Survey-4 (NFHS-4), the research sample included 176,255 children aged 0 to 59 months. Bivariate and multivariate techniques were used to analyze children’s risk factors for overweight/obesity. We identified that the prevalence of overweight/obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…These observed differences highlights that there may be additional demographic, lifestyle, and biological risk factors for obesity that should be analyzed. Many of these risk factors have been examined in the literature, including increased intake of sugar, decreased exercise, increased sedentary activity, and decreased sleep 11,13,14,16,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observed differences highlights that there may be additional demographic, lifestyle, and biological risk factors for obesity that should be analyzed. Many of these risk factors have been examined in the literature, including increased intake of sugar, decreased exercise, increased sedentary activity, and decreased sleep 11,13,14,16,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identi ed major risk factors for obesity, including demographic factors (race, sex, age), lifestyle factors (exercise, sleep), and clinical comorbidities (hypertension, diabetes. Additionally, multiple studies have demonstrated the high prevalence of weight gain in the United States population and detailed the signi cant medical consequences of obesity related diseases such as coronary artery disease and type II diabetes [11][12][13][14][15][16][17] . Despite the recognition of long-term weight gain as an important public health issue, there is a paucity of studies studying the long-term weight gain and building models for long-term projection.…”
Section: Introductionmentioning
confidence: 99%
“…The indexes of physical development which describe nutritional wellness in children are ageappropriate weight (underweight), and age-appropriate height (wasting and stunting). Poor physical development is associated with poor nutrition which increases the likelihood of poor school performance, lower productivity as adults, chronic diseases, cardiovascular disease, diabetes, cancer and mental health Saha et al, 2022) [35] . Ekwochi et al, 2014 [15] observed a prevalence of anemia among the studied under-five children, especially among those of low social economic class.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence exhibits considerable variability across different regions and demographics within India, fluctuating between 3% and 22.8% among school children aged 6 to 16 years [1]. Moreover, the incidence of overweight children under the age of five has been on the rise, surging from 2.1% (during 2015-2016) to 3.4% (throughout 2019-2021) [4]. Numerous studies have posited potential causes for this upward trend in overweight and obesity among Indian children, with attributing factors such as inadequate physical activity, prolonged television viewing, urban residence, and socioeconomic status within families [4].…”
Section: Statistics On Childhood Obesity Ratesmentioning
confidence: 99%